Challenges of The Housing People's Business Credit Program Policy in Encouraging the Empowerment of MSMES - Adhi Prasetyo Satriyo Wibowo (Jurnal Budget : Isu dan Masalah Keuangan Negara, 2025)
The Housing People's Business Credit Program, regulated under the Coordinating Minister for Economic Affairs Regulation Number 13 of 2025, aims to integrate UMKM empowerment into the national housing ecosystem to reduce the housing backlog of 12-15 million units and enhance productivity among small developers, contractors, and building material suppliers. Data were collected through a literature review, analyzing policy documents, scientific journals, and regulations related to MSMEs and the Small and Medium Enterprises Business Credit (KUR). Sources were selected based on thematic relevance and publication period (2015–2025) to ensure topicality. The findings highlight key obstacles, including regulations, limited access to financing, low financial literacy and human resource quality, inter-agency coordination, minimal digital technology adoption, and the absence of a unified database, leading to inaccurate mapping. The program offers an innovative scheme with a ceiling of up to IDR 20 billion on the supply side and IDR 500 million on the demand side, accompanied by a 5-6% interest subsidy. The conclusions emphasize the need for measured policy adjustments, cross-sectoral collaboration, and regular monitoring to reduce Non-Performing Loans (NPLs) to 5.2%, increase labor absorption, and strengthen the competitiveness of MSMEs in the housing sector.